2017
DOI: 10.1002/ece3.2713
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the history and ecological context of Wolbachia double infection in a specialist host (Urophora cardui)—parasitoid (Eurytoma serratulae) system

Abstract: The endosymbiotic bacterium Wolbachia is the most widespread bacteria in insects, yet the ecology of novel acquisitions in natural host populations is poorly understood. Using temporal data separated by 12 years, I tested the hypothesis that immigration of a parasitoid wasp led to transmission of its Wolbachia strain to its dipteran host, resulting in double‐strain infection, and I used geographic and community surveys to explore the history of transmission in fly and parasitoid. Double infection in the fly ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 69 publications
0
17
0
Order By: Relevance
“…Horizontal transmission is important for Wolbachia in extending their host range (Sudakaran et al, 2017). A common view is that horizontal transfer of Wolbachia requires intimate between‐species relationships (Johannesen, 2017). Transmission through the host‐parasitoid relationship is probably the main form of horizontal transmission and several reports have provided direct evidence (Heath et al, 1999; Vavre et al, 1999; Haine et al, 2005; Yang et al, 2013; Johannesen, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Horizontal transmission is important for Wolbachia in extending their host range (Sudakaran et al, 2017). A common view is that horizontal transfer of Wolbachia requires intimate between‐species relationships (Johannesen, 2017). Transmission through the host‐parasitoid relationship is probably the main form of horizontal transmission and several reports have provided direct evidence (Heath et al, 1999; Vavre et al, 1999; Haine et al, 2005; Yang et al, 2013; Johannesen, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Transmission through the host‐parasitoid relationship is probably the main form of horizontal transmission. Several studies have found the host and the parasitoid to be infected by the same Wolbachia strain, e.g., in Drosophila ‐parasitoid communities (Vavre et al, 1999; Haine et al, 2005), in gall wasp‐parasitoid communities (Yang et al, 2013), and in tephritid fly‐parasitoid communities (Johannesen, 2017). Parasitoids may acquire infection while developing inside an infected host (Heath et al, 1999; Chiel et al, 2009) and may also serve as phoretic vectors, spreading Wolbachia from infected to uninfected hosts (Gehrer & Vorburger, 2012; Ahmed et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…No direct evidence of Wolbachia transmission via parasitoids exists in tephritids, but sharing of Wolbachia strains between a parasitoid and several sympatric tephritids [144, 153] is consistent with parasitoid-mediated transmission, or transmission from tephritid host to parasitoid [176]. The potential for horizontal transfer of Wolbachia among tephritids via parasitoids is high, due to the multiple instances where a single parasitoid utilizes several different tephritid host species [177179].…”
Section: Wolbachia In Tephritidsmentioning
confidence: 99%
“…Although host-Wolbachia codivergence is relatively common between Nematode hosts and their Wolbachia strains, similar examples of co-divergence between insect hosts and their Wolbachia strains remain scarce [2, 3, but see 4]. These patterns thus suggest that Wolbachia may have jump jumped horizontally between host species throughout the ~ 400 million years of the symbiont evolutionary history [3,[5][6][7][8]. Hybridization events, followed by introgression between closely related species have been shown to support the interspecies transfer of various genetic entities, including Wolbachia [9][10][11].…”
Section: Introductionmentioning
confidence: 99%